Optimización de la gestión de procesos aplicando un Customer Relationship Management (crm) comercial - Corrales Martínez, Narciza Monserrath (2024)
In this research project, an exhaustive exploration of commercial Customer Relationship Management (CRM) was carried out, so it was identified that this tool is commonly used in the business environment to manage multiple leads, maintaining traceability and management of several sales channels simultaneously. However, within this research project, the alternative application of a CRM was proposed, within the management of pending and follow-up activities, coming from several communication sources.